Perovskite solar cell and preparation method thereof
By using water-based carbon electrode slurry and hydrophobic hydroxyethyl cellulose, the internal short circuit problem that perovskite solar cells are often encountered during the preparation process is solved, and efficient photoelectric conversion and low-cost production process are achieved.
Patent Information
- Application Number
- CN202411998273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Mesoporous perovskite solar cells often encounter internal short circuit problems during the preparation process, resulting in a decrease in battery efficiency.
Using water-based carbon electrode slurry, hydrophobic hydroxyethyl cellulose is used as a thickener and binder to organize the penetration of the carbon slurry to the insulating layer, thereby preventing the device from being short-circuited.
The high leakage resistance and internal short circuit of perovskite solar cells are achieved, and the photoelectric conversion efficiency is improved.
Smart Images

Figure BDA0005225414500000111 
Figure HDA0005225414550000011 
Figure HDA0005225414550000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] With the advantages of high theoretical conversion efficiency and low cost, perovskite solar cells have great potential for research and development and application. Mesoporous perovskite solar cells are perovskite solar cells with at least one charge transport layer (electron transport layer, hole transport layer) as a mesoporous structure, which has significant advantages in increasing the contact area between perovskite and charge transport layer, increasing carrier separation, and improving the photoelectric conversion efficiency of the cell.
[0003] A representative mesoporous perovskite solar cell technology is a three-layer mesoporous carbon electrode mesoporous perovskite solar cell (see references J.Phys.Chem.Lett.2014,5,17,2927-2934, Nano Lett.2014,14,2,1000-1004, patent CN202210806436.4, etc.). In the preparation process of the battery, the electron transport layer slurry, the insulating layer slurry, and the carbon slurry are first coated on the FTO substrate in sequence, and the pine alcohol in the slurry is heated to remove and the ethyl cellulose is decomposed and volatilized to form pores to form a "blank device", and then the perovskite precursor solution is dripped into the blank device, and the perovskite is heated and evaporated to induce crystallization of the perovskite to make a battery device. This method does not require expensive hole transport materials such as Spiro-OMeTAD, which greatly reduces the cost. At the same time, the carbon electrode does not react chemically with the perovskite, which greatly improves the stability of the battery device.
[0004] However, the slurry of mesoporous perovskite solar cells generally uses pine oil as a solvent, ethyl cellulose and organic acid as thickeners and surfactants, respectively, and is made by mixing, rotary evaporation and other processes. In the preparation process of three-layer mesoporous carbon electrode perovskite solar cells, the problem of internal short circuit is often encountered. After the carbon slurry is coated on the insulating layer slurry, due to the strong solubility and permeability of pine oil, the carbon slurry is easy to corrode the insulating layer and contact the electron transport layer, causing the device to have an internal short circuit, which will greatly increase the leakage loss and cause the battery efficiency to drop significantly. In the previous production process, the method used was to cool the coated insulating layer, age it, and then apply the carbon slurry. This method can alleviate the corrosion of the insulating layer to a certain extent, but it cannot completely avoid the problem. Therefore, it is necessary to develop a method that can more effectively prevent the carbon electrode from penetrating the insulating layer and eliminate the internal short circuit of the battery to improve the efficiency of the device. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a perovskite solar cell and a preparation method thereof. The perovskite solar cell prepared by the present invention has high leakage resistance, no internal short circuit, and high photoelectric conversion efficiency.
[0006] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps:
[0007] A) coating an electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; then coating an insulating layer slurry on the electron transport layer, drying to form an insulating layer; then coating a carbon slurry on the insulating layer, heating and annealing to form a carbon electrode, and obtaining a blank device without perovskite;
[0008] The electron transport layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material; the insulating layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the carbon slurry is prepared from raw materials including water, a binder and a carbon material;
[0009] B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;
[0010] C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
[0011] Preferably, the dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol;
[0012] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL;
[0013] The volume of the ethanol is 1 to 3 times the volume of terpineol.
[0014] Preferably, the electron transport material comprises TiO2, SnO2 or ZnO;
[0015] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm;
[0016] In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.
[0017] Preferably, the method for preparing the electron transport layer slurry comprises the following steps:
[0018] Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry;
[0019] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
[0020] Preferably, the insulating layer material includes ZrO2, Al2O3 or SiO2;
[0021] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm;
[0022] In the raw materials for preparing the insulating layer slurry, the usage ratio of the insulating layer material to the pinene alcohol is 150-450 mg:1 mL.
[0023] Preferably, the method for preparing the insulating layer slurry comprises the following steps:
[0024] Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry;
[0025] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
[0026] Preferably, the carbon material is selected from graphite and conductive carbon black;
[0027] The mass of the carbon material is 15% to 50% of the mass of water;
[0028] The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the mass of the binder is 0.5% to 5% of the mass of water.
[0029] Preferably, the coating thickness of the electron transport layer slurry is 0.5 to 2 μm;
[0030] The coating thickness of the insulating layer slurry is 1 to 3 μm;
[0031] The coating thickness of the carbon slurry is 10 to 50 μm.
[0032] Preferably, in step B), in the perovskite precursor solution, the solvent includes at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br- and Cl - At least one of;
[0033] The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L;
[0034] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ;
[0035] The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.
[0036] The present invention also provides a perovskite solar cell prepared by the preparation method described above.
[0037] The key reason why the carbon electrode corrodes the insulating layer is that the carbon slurry contains highly soluble solvents such as pine alcohol. If such highly soluble solvents are not used in the preparation process of the carbon electrode, the corrosion problem of the insulating layer may be eliminated. In the present invention, hydrophobic hydroxyethyl cellulose is used as a thickener and binder in the insulating layer slurry, and water is used as a solvent to prepare the carbon slurry. The hydrophobic effect of ethyl cellulose is used to organize the penetration of the carbon slurry into the insulating layer, thereby preventing the device from short-circuiting. The finally prepared perovskite solar cell has a high leakage resistance, no internal short circuit, and high photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A comparison diagram of the coating method of the present invention and the conventional perovskite solar cell;
[0039] Figure 2 IV test curves of the mesoporous perovskite solar cells obtained in Examples 1-2 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention provides a method for preparing a perovskite solar cell, comprising the following steps:
[0042] A) coating an electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; then coating an insulating layer slurry on the electron transport layer, drying to form an insulating layer; then coating a carbon slurry on the insulating layer, heating and annealing to form a carbon electrode, and obtaining a blank device without perovskite;
[0043] The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the raw materials for preparing the carbon slurry are composed of water, a binder and a carbon material;
[0044] B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;
[0045] C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
[0046] In step A):
[0047] The electron transport layer slurry is coated on the conductive substrate, and heated and annealed to form an electron transport layer; the insulating layer slurry is then coated on the electron transport layer, and dried to form an insulating layer; the carbon slurry is then coated on the insulating layer, and heated and annealed to form a carbon electrode, thereby obtaining a blank device without perovskite;
[0048] The raw materials for preparing the electron transport layer slurry are composed of pine alcohol, dispersant, thickener, ethanol and electron transport material; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, dispersant, thickener, ethanol and insulating layer material; the raw materials for preparing the carbon slurry are composed of water, binder and carbon material.
[0049] About conductive substrate:
[0050] The conductive substrate includes FTO glass, ITO glass or any other transparent conductive substrate, preferably FTO glass. The film thickness of the conductive substrate is 200-500nm, preferably 350nm.
[0051] About the electron transport layer:
[0052] The electron transport material includes TiO2, SnO2, ZnO or any other n-type semiconductor material.
[0053] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.
[0054] The usage ratio of the electron transport material to the pineol is 50-200 mg:1 mL, preferably 100 mg:1 mL.
[0055] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, such as 4%.
[0056] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; specifically, ethyl cellulose and polyvinyl alcohol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, such as 150 mg:1 mL.
[0057] The volume of the ethanol is 1 to 2 times, preferably 1.5 times, the volume of terpineol.
[0058] The method for preparing the electron transport layer slurry comprises the following steps:
[0059] The pine alcohol, dispersant, thickener, ethanol and electron transport material are mixed, and the ethanol is removed by rotary evaporation to obtain an electron transport layer slurry.
[0060] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0061] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 40 to 60° C., preferably 50° C.; and a time of 4 to 12 h, preferably 6 h.
[0062] The coating thickness of the electron transport layer slurry is 0.5-2 μm, preferably 0.8 μm.
[0063] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.
[0064] The heating annealing temperature is 400-600° C., preferably 500° C.; the time is 15-60 min, preferably 40 min.
[0065] About the insulation layer:
[0066] The insulating layer material includes ZrO2, Al2O3, SiO2 or any other insulating material.
[0067] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.
[0068] The usage ratio of the insulating layer material to the pine alcohol is 150-450 mg:1 mL, for example, 250 mg:1 mL.
[0069] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.
[0070] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; specifically, ethyl cellulose and polyvinyl alcohol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, such as 150 mg:1 mL.
[0071] The volume of the ethanol is 1 to 2 times, preferably 1.5 times, the volume of terpineol.
[0072] The method for preparing the insulating layer slurry comprises the following steps:
[0073] The pine alcohol, dispersant, thickener, ethanol and insulating layer material are mixed, and the ethanol is removed by rotary evaporation to obtain insulating layer slurry.
[0074] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0075] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 40 to 60° C., preferably 50° C.; and a time of 4 to 12 h, preferably 6 h.
[0076] The coating thickness of the insulating layer slurry is 1-3 μm, preferably 1.5 μm.
[0077] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.
[0078] The drying temperature is 60-100° C., preferably 80° C.; the drying time is 15-60 min, preferably 40 min.
[0079] About Carbon Electrode:
[0080] The carbon material is selected from graphite and conductive carbon black; preferably, graphite with a particle size of 5 to 10 μm (preferably 7 μm) and conductive carbon black with a particle size of 20 to 50 nm (preferably 30 nm) are used in a mass ratio of 4:1.
[0081] The mass ratio of the carbon material to the water is 150-750 mg:1 mL, preferably 500 mg:1 mL.
[0082] The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the average molecular weight of the binder is 5000-20000, preferably 10000; the mass ratio of the binder to water is 5-50 mg:1 mL, preferably 20 mg:1 mL.
[0083] The preparation method of the carbon slurry comprises the following steps:
[0084] Water, a binder and a carbon material are mixed to obtain a carbon slurry.
[0085] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0086] The coating thickness of the carbon slurry is 10-50 μm, preferably 25 μm.
[0087] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.
[0088] Before the heating, the process further includes drying, wherein the drying is used to remove moisture.
[0089] The heating annealing temperature is 300-500° C., preferably 400° C., and the time is 15-60 min, preferably 40 min. The heating is used to remove the binder.
[0090] In step B):
[0091] The perovskite precursor solution is dripped onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing is performed to obtain a device containing perovskite.
[0092] In the perovskite precursor solution, the solvent includes at least one of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); the solute is ABX3 (wherein A is at least one of methylamine (MA) ion, formamidine (FA) ion and cesium (Cs) ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of the following), such as MA 0.4 FA 0.6 In certain embodiments, the solvent comprises DMF and DMSO in a volume ratio of 4:1.
[0093] The concentration of the perovskite precursor solution is 1.0-1.5 mol / L, preferably 1.2 mol / L.
[0094] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 , preferably 3 μL / cm 2 .
[0095] The annealing temperature is 60-120°C, and the time is 4-24h; preferably, when the annealing temperature is 60°C / 80°C / 100°C / 120°C, the corresponding time is 24h / 16h / 8h / 4h. The annealing is used to remove the solvent in the perovskite precursor solution and precipitate the perovskite.
[0096] In step C):
[0097] A back plate is added to the bottom electrode of the device obtained in step B), wires are connected, and sealant is applied to obtain a mesoporous perovskite solar cell.
[0098] The back panel is made of glass, organic glass or other airtight panels.
[0099] The present invention has no particular limitation on the method of connecting the wires, and any method of connecting the wires well known to those skilled in the art may be used.
[0100] The sealant can be commercial sealant, and common ingredients include epoxy resin or ethylene-vinyl acetate copolymer.
[0101] Figure 1 : is a comparison diagram of the coating method of the present invention and the conventional perovskite solar cell. Figure 1 It can be seen that the traditional coating process is to coat the carbon electrode alcohol-based slurry on the ZrO2 insulating layer, which will cause the carbon slurry to dissolve and pierce the ZrO2 insulating layer, resulting in device short circuit and reduced efficiency; the core point of the method adopted by the present invention is to use water-based carbon electrode slurry, which cannot produce dissolution and corrosion on the surface of the hydrophobic alcohol-based ZrO2 insulating layer, thus eliminating the situation where the carbon slurry pierces the insulating layer, preventing the device from short circuiting, thereby improving the device efficiency.
[0102] Beneficial effects:
[0103] 1) Can effectively prevent battery short circuit: Since the carbon electrode is made of water-based carbon slurry, it will not corrode the insulating layer, thus preventing the device from short circuiting.
[0104] 2) Simple process: low equipment cost, mild production process, low risk and easy operation.
[0105] 3) Low cost: The main raw materials used, such as water, polyvinyl alcohol, carboxymethyl cellulose, etc., are all commonly used and cheap raw materials. No high-priced raw materials or equipment are required, thus reducing costs.
[0106] 4) High device performance: Since the device obtained by this method does not have an internal short circuit, the leakage loss is reduced, thereby ensuring the photoelectric conversion efficiency of the solar cell.
[0107] 5) It is conducive to large-scale production: large-area perovskite solar cells are more sensitive to short-circuit problems. The present invention greatly reduces the risk of short circuits in the battery, which is conducive to the manufacture of large-area perovskite solar cells.
[0108] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0109] In order to further illustrate the present invention, a perovskite solar cell and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the protection scope of the present invention.
[0110] Example 1
[0111] 1) Preparation of electron transport layer slurry:
[0112] Use 20 mL of pineol, 40 mL of ethanol, 0.2 mL, 0.4 mL, 0.2 mL of acetylacetone, acetic acid and lauric acid respectively, 2 g, 1 g of ethyl cellulose (average molecular weight 10,000) and polyvinyl alcohol (average molecular weight 10,000), 2 g of TiO2 with a particle size of 30-50 nm, and perform high shear emulsification for 1 h (speed 6,000 rpm), ball milling for 24 h (speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) to remove ethanol to obtain an electron transport layer slurry.
[0113] 2) Preparation of insulation layer slurry:
[0114] Use 20mL of pineol, 40mL of ethanol, 0.2mL, 0.4mL, 0.2mL of acetylacetone, acetic acid and lauric acid respectively, 2g and 1g of ethyl cellulose (average molecular weight 10000) and polyvinyl alcohol (average molecular weight 10000) respectively, 5g of ZrO2 with a particle size of 30-50nm, and perform high shear emulsification for 1h (speed 6000rpm), ball milling for 24h (speed 300rpm), ultrasound for 1h, and rotary evaporation at 45℃ for 6h (pressure 20mbar) to remove ethanol to obtain an insulating layer slurry.
[0115] 3) Preparation of carbon slurry:
[0116] Use 30 mL of water, 0.6 g of polyvinyl alcohol (average molecular weight 10,000), 0.6 g of carboxymethyl cellulose, 12 g of 7 μm graphite and 3 g of 30 nm carbon black, and perform high shear emulsification for 1 h (rotation speed 6,000 rpm), ball milling for 24 h (rotation speed 300 rpm), and ultrasound for 1 h to make a carbon slurry.
[0117] 4) coating the electron transport layer slurry on the conductive substrate with a coating thickness of 0.8 μm, and heating at 500°C for 40 min to form an electron transport layer; then coating the insulating layer slurry on the electron transport layer with a coating thickness of 1500 nm (1.5 μm), heating at 80°C for 40 min to form an insulating layer; then coating the carbon slurry on the insulating layer with a coating thickness of 40 μm, drying at 100°C, and then heating at 400°C for 40 min to remove the binder, forming a carbon electrode, and obtaining a blank device without perovskite.
[0118] 5) The perovskite precursor solution (solvent includes DMF and DMSO, volume ratio is 4:1; solute is MA 0.4 FA 0.6 PbI3, concentration of 1.2 mol / L) was added dropwise onto the bottom electrode of the blank device (the amount added was 3 μL / cm 2 ), after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing is performed at 80°C for 16h to obtain a perovskite-containing device.
[0119] 6) Covering the bottom electrode of the device obtained in step 5) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
[0120] Example 2
[0121] The difference from Example 1 is:
[0122] In step 3), 0.6 g each of polyvinyl alcohol (average molecular weight 10,000) and carboxymethyl cellulose was replaced with 1.2 g of hydroxyethyl cellulose;
[0123] In step 4), the thickness of the carbon slurry coating was changed from 40 μm to 80 μm.
[0124] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.
[0125] Comparative Example 1
[0126] The difference from Example 1 is:
[0127] Step 3): Preparation of carbon slurry:
[0128] Use 20 mL of pine alcohol, 40 mL of ethanol, 0.2 mL of acetylacetone, 0.4 mL of acetic acid and 0.2 mL of lauric acid respectively, 2 g of ethyl cellulose (average molecular weight 10000) and 1 g of polyvinyl alcohol (average molecular weight 10000), 12 g of 7 μm graphite and 3 g of 30 nm carbon black respectively, and carry out high shear emulsification for 1 h (rotation speed 6000 rpm), ball milling for 24 h (rotation speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) in sequence to obtain a carbon slurry.
[0129] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.
[0130] Comparative Example 2
[0131] The difference from Example 1 is:
[0132] Step 2): Preparation of insulation layer slurry:
[0133] Use 30 mL of water, 0.6 g of polyvinyl alcohol (average molecular weight 10,000), 0.6 g of carboxymethyl cellulose, and 5 g of ZrO2 with a particle size of 30 to 50 nm, and perform high shear emulsification for 1 h (rotation speed 6,000 rpm), ball milling for 24 h (rotation speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45°C for 6 h (pressure 20 mbar) to remove ethanol to obtain an insulating layer slurry.
[0134] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.
[0135] Figure 2 The IV test curves of the mesoporous perovskite solar cells obtained in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2. The IV test uses a steady-state solar light source, the test scan range is 1V to 0V, reverse scanning is used, and the scan rate is 50mV / s.
[0136] from Figure 2 It can be seen that the voltage and current of the embodiment are significantly higher than those of the comparative example.
[0137] The electrical properties of the mesoporous perovskite solar cells obtained in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 were tested, and the results are shown in Table 1. The test conditions are the same as Figure 2 .
[0138] Table 1 Electrical performance test results of mesoporous perovskite solar cells obtained in Examples 1-2 and Comparative Examples 1-2
[0139]
[0140] As can be seen from Table 1, after adopting the hydrophobic ZrO2+ water-based carbon coating method of the present invention, the leakage resistance of the device is greatly increased, the leakage loss of the device is suppressed, thereby improving the voltage and current of the device, and finally the photoelectric conversion efficiency of the device is improved by about 7 percentage points.
[0141] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a perovskite solar cell, comprising the following steps: A) coating the electron transport layer slurry on a conductive substrate, heating and annealing to form an electron transport layer; Then, the insulating layer slurry is coated on the electron transport layer, and dried to form an insulating layer; then, the carbon slurry is coated on the insulating layer, and heated and annealed to form a carbon electrode, thereby obtaining a blank device without perovskite; The electron transport layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material; the insulating layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an insulating layer material; the carbon slurry is prepared from raw materials including water, a binder and a carbon material; B) dropping a perovskite precursor solution onto the carbon electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device; C) Covering the bottom electrode of the device obtained in step B) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
2. The preparation method according to claim 1, characterized in that: The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol; The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL; The volume of the ethanol is 1 to 3 times the volume of terpineol.
3. The preparation method according to claim 1, characterized in that: The electron transport material includes TiO2, SnO2 or ZnO; The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.
4. The preparation method according to claim 1, characterized in that: The method for preparing the electron transport layer slurry comprises the following steps: Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
5. The preparation method according to claim 1, characterized in that: The insulating layer material includes ZrO2, Al2O3 or SiO2; The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; In the raw materials for preparing the insulating layer slurry, the usage ratio of the insulating layer material to the pinene alcohol is 150-450 mg:1 mL.
6. The preparation method according to claim 1, characterized in that: The method for preparing the insulating layer slurry comprises the following steps: Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
7. The preparation method according to claim 1, characterized in that: The carbon material is selected from graphite and conductive carbon black; The mass of the carbon material is 15% to 50% of the mass of water; The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the mass of the binder is 0.5% to 5% of the mass of water.
8. The preparation method according to claim 1, characterized in that: The coating thickness of the electron transport layer slurry is 0.5 to 2 μm; The coating thickness of the insulating layer slurry is 1 to 3 μm; The coating thickness of the carbon slurry is 10 to 50 μm.
9. The preparation method according to claim 1, characterized in that: In step B), the perovskite precursor solution comprises a solvent including at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of; The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L; The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ; The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.
10. A perovskite solar cell prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Perovskite solar cell and carbon slurry and preparation method thereof
CN115064301A
Mesoporous perovskite solar cell and preparation method thereof
CN117320463A
Perovskite solar cell and preparation method thereof
CN117320464A
Mesoporous perovskite solar cell and preparation method thereof
CN117320465A
Three-mesoporous carbon-based perovskite solar cell and preparation method thereof
CN117377330A
Cited By
Tantalum carbide coating, preparation method thereof and tantalum carbide product
CN120229970A
Tantalum carbide coating and method of making same, tantalum carbide article
CN120229970B